Propagation channel characterization for mobile communication based on measurement campaign and simulation - Olaonipekun Oluwafemi Erunkulu; Thula Innocent Gwebu; Adamu Murtala Zungeru; Caspar Lebekwe; Mosalaosi Modisa (Results in Engineering, 2023)
Predicting the coverage area of mobile networks across various frequency bands is a critical concern in wireless communication. Each frequency band exhibits distinct propagation characteristics that directly influence the network coverage. Therefore, the use of the appropriate propagation models, whether through simulation or measurement-based approaches, is essential for accurate signal strength prediction in different environments and scenarios. In this study, we focus on the analysis and comparison of propagation channel characterization for mobile communication within the sub-6GHz frequency range. Our research involved outdoor measurement campaigns and ray-tracing simulations conducted at the Botswana International University of Science and Technology, covering distances up to 213 m. We then conducted an in-depth investigation and comparative analysis of the measured and simulated data for the propagation channel. Additionally, we derived a characterization model for the closed-in free space reference distance (CI) model based on measured and simulated data. Finally, we employed the root-mean-square error (RMSE) as a quantitative assessment of the performance of the characterized models. Notably, our findings revealed that the derived Close-in model based on measured data outperformed that of the simulations, exhibiting the lowest RMSE values of 3.56 dB, 4.20 dB, and 7.87 dB for location-1 line-of-sight, location-2 line-of-sight, and non-line-of-sight scenarios, respectively. These results hold significant potential for the development of precise path loss models that can effectively predict and optimize the coverage area of mobile communication systems across various real-world scenarios and environments.